ISLAMIC PHILOSOPHY PERSPECTIVE ON BIRR AL-WALIDAIN - Wijaya, Mirza Mahbub; Mahmutarom; Ekaningrum, Ifada Retno; Nurcholish, Nanang (Living Islam: Journal of Islamic Discourses, 2022)
Along with the times, not a few people are getting away from the values of the Qur’an. This includes the causes of moral decline. This study aims to determine the philosophical concept of birr al-walidain in Surah al-Ahqof verse 15. This study is qualitative research with the type of library research. The data collection technique used is technical documentation. The data analysis used was the tahlili interpretation method. The results of this study obtained, ontologically, the concept of birr al-walidain is an intermediary for devotion to Allah. In the epistemological dimension, the role model of parents is the main source in birr al-walidain. Whereas in the axiological dimension, the concept of birr al-walidain is included in the transcendental virtue which is obtained through character strength (psychological composition, both process, and mechanism) with spirituality (religion, faith, and purpose)